Case report: A successful clinical experience of transplantation of liver and kidney from a donor with myelodysplastic syndromes - Huang, Kang; Zhang, Qiuyan; Wu, Sanyun; Zhou, Lihua; Liang, Wenjin; Hu, Xiaoyan; Ye, Shaojun; Zhou, Wei (Frontiers in Immunology, 2024)
With a shortage of organs for transplant, the use of marginal donors can be an effective measure to meet the shortfall. Myelodysplastic syndromes (MDS) are considered an absolute contraindication for organ donation because of the high invasive potential. Currently, organ transplantation from donors with a past history of MDS has not been reported. In this paper, we report the successful clinical experience of one liver transplantation and two kidney transplantations, with organs donated by a 39-year-old patient diagnosed with a past history of MDS following intracranial hemorrhage. Four and a half years after transplantation, the three recipients are all doing well. However, it is still not clear to what extent organs donated by patients with a past history of MDS can be safely transplanted. This report provides support for the careful use of marginal donors. With effective treatment and full peer assessment, livers and kidneys from donors with a past history of MDS may be safely transplanted.